Case Report: Probable Cerebral Amyloid Angiopathy-Related Inflammation During Bevacizumab Treatment for Metastatic Cervical Cancer - Koudriavtseva, Tatiana; Lorenzano, Svetlana; Anelli, Vincenzo; Sergi, Domenico; Stefanile, Annunziata; Di Domenico, Enea Gino; Maschio, Marta; Galiè, Edvina; Piantadosi, Carlo (Frontiers in Oncology, 2021)
Bevacizumab is an anti-angiogenic monoclonal antibody targeting Vascular Endothelial Growth Factor (VEGF) that induces the proliferation and migration of vascular endothelial cells thus, promotes vasculogenesis. Bevacizumab inhibits cancer angiogenesis, which is fundamental for either tumor development, its exponential growth, or metastatic spread by supplying nutrients and oxygen. We report a new possible adverse event of bevacizumab, a Cerebral Amyloid Angiopathy-Related Inflammation (CAARI), in a 72-year-old woman with metastatic cervical cancer. After 6 cycles every three weeks of chemotherapy (cisplatin, paclitaxel, bevacizumab) and following two maintenance bevacizumab administrations, the patient presented a worsening confusional state. The MRI scan showed bilateral asymmetric temporo-parieto-occipital hyperintensity with numerous cortical microbleeds indicative of a CAARI. After stopping bevacizumab treatment, steroid therapy was administered resulting in rapid clinical improvement. The subsequent neurological and oncological follow up was negative for recurrence. The patient was a heterozygote carrier for apolipoprotein-E ɛ4 that increases the risk of sporadic Cerebral Amyloid Angiopathy (CAA), which is characterized by beta-amyloid accumulation and fibrinoid necrosis in cerebral vasculature leading to micro/macrohemorrhages and dementia. Moreover, CAA is present in 30% of people aged over 60 years without dementia. In the brains of CAA patients, there is a proinflammatory state with cerebrovascular endothelial cell alteration and elevated levels of either adhesion molecules or inflammatory interleukins that increase the blood–brain barrier permeability. Moreover, CAARI is an inflammatory form of CAA. Inhibition of VEGF, which has anti-apoptotic, anti-inflammatory and pro-survival effects on endothelial cells, impairs their regenerative capacity and increases expression of proinflammatory genes leading to weakened supporting layers of blood vessels and, hence, to damaged vascular integrity. In our patient, bevacizumab administration may have further increase permeability of cerebral microvasculature likely impaired by an underlying, asymptomatic CAA. To our knowledge, this is the first case reporting on the development of probable CAARI during bevacizumab treatment, which should alert the clinicians in case of neurological symptom onset in older patients under anti-angiogenic therapy.